The lost symbol a novel - Brown, Dan 1964- (Doubleday, 2009)
In this stunning follow-up to the global phenomenon The Da Vinci Code, Dan Brown demonstrates once again why he is the world's most popular thriller writer. The Lost Symbol is a masterstroke of storytelling--a deadly race through a real-world labyrinth of codes, secrets, and unseen truths . . . all under the watchful eye of Brown's most terrifying villain to date. Set within the hidden chambers, tunnels, and temples of Washington, D.C., The Lost Symbol accelerates through a startling landscape toward an unthinkable finale.